Livestock and Fish animal genetics flagship review and plans - Benzie, John A.H.; Okeyo Mwai, Ally; Haile, Aynalem (International Livestock Research Institute, 2015)
John Benzie to the CGIAR Research Program on Livestock and Fish review and planning meeting, 23-26 March 2015